Endometrial histopathology results and evaluation of endometrial cancer risk in geriatric women - Günakan, Emre; Atak, Zeliha; Albayrak, Mustafa; Kurban, Yüksel; Şimşek, Gülçin G. (Menopause Review/Przegląd Menopauzalny, 2018)
The incidence of premalignant and malignant endometrial disorders increases during the postmenopausal period. In the literature, endometrial disorders are usually discussed in the context of menopausal status. But there are limited data regarding endometrial disorders in geriatric patients. Early diagnosis of endometrial cancers with aggressive behaviour that increases during the geriatric period may allow simpler treatment options and also decrease the treatment-associated morbidity risk. Records of geriatric patients who underwent an endometrial histopathological evaluation between 2011 and 2016 were evaluated. Clinical findings, transvaginal ultrasonography findings, endometrial sampling methods, and histopathological results were evaluated. A total of 188 patients were included in the study (mean age 70.3 ±5.6 years). The most common histopathological results were endometrial polyp, atrophic endometrium, and surface epithelium (26.6%, 22.3%, and 12.8%, respectively). None of the 57 patients without vaginal bleeding had endometrial cancer. In 131 patients with vaginal bleeding, mean endometrial thickness was 9.8 ±8.1 mm (2-49 mm) and the rate of endometrial disorders was 56.5% (74 patients). Endometrial cancer was diagnosed in 19 patients (10.1%), and 36.8% of them had non-endometrioid cancers. The presence of vaginal bleeding was significantly associated with the diagnosis of endometrial cancer and any endometrial disorder (p = 0.001 and p = 0.000, respectively). The incidence of non-endometrioid endometrial cancers increased in the geriatric period. An endometrial histopathological examination should be considered, especially for patients with a history of vaginal bleeding. Further investigation of the endometrial thickness cut-off levels in the geriatric period will contribute to the literature.